Trade-offs in Achieving Human Development Goals for Bangladesh - Yeasmin Sayeed (Örebro University School of Business, 2014)
Even though Bangladesh has made progress towards reaching some of the Millennium Development Goals (MDGs), it is still a major challenge for the government to further reduce poverty and improve human developments, in particular achieving a 100 percent primary-school completion rate. As foreign aid is declining, resources need to be mobilized either by taxation or borrowing. Each funding option has drawbacks so it is important when government now chooses how to proceed to have an apprehension of the tradeoffs involved. Also issues arise in whether the composition of public spending should lean towards investment in human capital or infrastructural capital. In this paper, we apply the MAMS computable general equilibrium model developed by the World Bank to do a retrospective analysis study comparing a baseline scenario that mimics the actual development during the period 2005 - 2015 with four counterfactual scenarios in which the four most important MDG targets (education, child mortality, maternal mortality, water and sanitation) are achieved, based on either taxation, foreign borrowing, aid or domestic borrowing. Further, we compare the baseline with three public spending reallocation scenarios. We find that full achievement of these goals would have led to a GDP loss of 17 percent and 10 percent from domestic borrowing or taxation, respectively. For public spending composition we find that the marginal impact on achievement of the targets from reallocating public spending from infrastructure investment to human development sectors in Bangladesh is small.
Keywords: H52; H54; O11; O15; 330; MDGs; Infrastructure; Growth; CGE; MAMS